2018
DOI: 10.1128/jmbe.v19i1.1440
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Undergraduates’ Perceptions of Science in Courses Taught Using the CREATE Strategy

Abstract: Many science educators agree that 21st century students need to develop mature scientific thinking skills. Unsurprisingly, students’ and experts’ perceptions about the nature of scientific knowledge differ. Moreover, students’ naïve and entrenched epistemologies can preclude their development toward “thinking like scientists.” Novel teaching approaches that guide students toward more mature perceptions may be needed to support their development of scientific thinking skills. To address such issues, physics edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
2
19
1
1
Order By: Relevance
“…Results from this study align with others who found that various forms of inquiry improved students' perceptions (Hoskins & Gottesman, 2018;Kazempour, Amirshokoohi, & Harwood, 2012;Majerich & Schmuckler, 2007;McArthur & Van Hook, 2004). Further, Houghton (2004) stated that providing intellectual independence and letting students learn from each other can improve their perceptions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results from this study align with others who found that various forms of inquiry improved students' perceptions (Hoskins & Gottesman, 2018;Kazempour, Amirshokoohi, & Harwood, 2012;Majerich & Schmuckler, 2007;McArthur & Van Hook, 2004). Further, Houghton (2004) stated that providing intellectual independence and letting students learn from each other can improve their perceptions.…”
Section: Discussionsupporting
confidence: 86%
“…Duran, McArthur, and Van Hook (2004) investigated the impact of an inquiry college physics class on students' perceptions and found significantly more positive perceptions than those in the traditional lecture class. Another study by Hoskins and Gottesman (2018) used "CREATE (Consider, Read, Elucidate hypotheses, Analyze and interpret the data, Think of the next Experiment)" (p. 1) instructional approach to improve students' perceptions of a biology course. There was a significant shift from novice-like views to expert-like views within a semester of using CREATE.…”
Section: Studies About Students' Perceptionmentioning
confidence: 99%
“…We compared students who experienced the CREATE module with those in different sections of the same course taught without CREATE. In this way, we tested the hypothesis that students who experienced a single CREATE module taught over a few class periods would make gains in scientific literacy and selfefficacy while also experiencing positive shifts in epistemological beliefs about scientific skills and knowledge (18)(19)(20)(21)(22)(23)(24). Our hypothesis was partially supported by the data in that students in the CREATE sections made significant gains in self-efficacy but did not gain transferable data analysis skills.…”
Section: Introductionmentioning
confidence: 92%
“…Taking advantage of the narrative nature of science, the strategy uses intensive analysis of interrelated papers to demystify and humanize the research process. Students in CREATE courses have made a variety of cognitive and affective gains, in first-year (19,20) and upper-level electives (18,21) at a minorityserving institution, as well as in a variety of four-year (22,23) and two-year (24) college/university settings. All implementations of CREATE tested to date were semester-or quarter-long topical courses taught by faculty who learned the CREATE technique through multi-day faculty development workshops (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Students develop core concepts and competencies in biological sciences through reading discussing primary literature and by systematically decoding figures, tables, and narratives in a scaffolded fashion (14,(21)(22)(23)(24)(25). CREATE has been successfully implemented by faculty across many institutional contexts (26) and has been shown to promote affective, cognitive, and epistemological development of diverse two-and four-year students (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%